Students' perception on the use of poetry for teaching speaking - Suwastini, Ni Komang Arie; Dewi, Gusti Putu Rustika (Electronic Journal of Education, Social Economics and Technology, 2023)
Poetry is rich in terms of its selectively chosen dictions that have to be read aloud to be enjoyed. This descriptive qualitative study investigated fourth-semester students' perception on the use of poetry to teach speaking. Students' perceptions were collected through an archives study comprising 75 students' essay projects about using poetry to teach speaking. The result indicated that 75 students perceived poetry is effective in developing six aspects of students' speaking skills, namely vocabulary, pronunciation, grammar, comprehension, confidence, and fluency. 41 (54.66%) students perceived that teaching speaking through poetry enriches students' vocabulary by representing unique words. 16 (21.33%) students perceived that using poetry to teach speaking practices students' pronunciation through poetry reading strategy. In terms of grammar mastery, 8 (10.66%) students believed that poetry was able to familiarize students with sentence structure. Four (5.33%) students perceived that through poetry analysis, students must comprehend and share their interpretation of the content and context used in the poems. There were 4 (5.33%) students perceived that poetry helps students be more confident in communication. Two (2.66%) students perceived that fluency in speaking could be trained using poetry by exposing students to the rhythm, making their intonation improved.